Construction of pY-Af Vector for Expression of Thermostable Î±-L-Arabinofuranosidase in Saccharomyces cerevisiae - Wirajana, I Nengah; Puspaningsih, Ni Nyoman Tri; Wasito, Eddy Bagus; Kusuma, Soekry Erfan; Kimura, Tetsuya; Sakka, Kazuo (ANNALES BOGORIENSES, 2010)
In this research,Â  constructionÂ  of expressionÂ  vectorÂ  for thermostable Î± -L-arabinofuranosidaseÂ  in Saccharomyces cerevisiae was conducted. BJ1824 was conducted TheÂ  Escherichia coli/S. cerevisiaeÂ  shuttle vector, pYES2 wasÂ  usedÂ  asÂ  parentalÂ  vectorÂ  inÂ  construction.Â  TheÂ  abfAÂ  geneÂ  encodingÂ  Î±-L- arabinofuranosidaseÂ  from GeobacillusÂ  thermoleovoransÂ  IT-08Â  wasÂ  amplifiedÂ  byÂ  PCR,Â  inÂ  whichÂ  theÂ  plasmidÂ  pTP510 wasÂ  usedÂ  asÂ  a template. The amplification product was treated withÂ  SacI and XhoI and then subcloned to the pYES2 vector, which was previously digested withÂ  SacI andÂ  XhoI. The recombinant plasmid was designated as pY-Af and propagatedÂ  firstÂ  inÂ  E.Â  coliÂ  Top 10,Â  andÂ  thenÂ  transformedÂ  intoÂ  S.Â  cerevisiaeÂ  BJ1824.Â  ForÂ  Î±- Larabinofuranosidase (AbfA) production, the yeast transformants were grown in YNBG selective medium and YPG rich medium, using galactose as an inducer. The AbfA activity was assayed by measuring the amount of p-nitrophenol (pNP) releasedÂ  fromÂ  p-nitrophenyl-Î±-L-arabinofuranosideÂ  (pNPA) substrate at pH 6.0 and 70 ï°CÂ  forÂ  30Â  min.Â  TheÂ  recombinantÂ  AbfAÂ  activityÂ  wasÂ  detectedÂ  inÂ  eitherÂ  ofÂ  cultureÂ  mediumÂ  (0.98%),Â  cellassociated (14.17%) and intracellular (84.85%) when recombinant yeast was grown in YPG rich medium.Key words:Â Î±-L-arabinofuranosidase; Saccharomyces cerevisiae; expression vector